Challenges of educational management in a pandemic context - Suarez Amaya, Wendolin (2021)
In recent times, an unprecedented event in contemporary history has disrupted social systems, exposing vulnerabilities in our educational system, mainly in economically disadvantaged areas. The covid- 19 arrived in an untimely manner and forced to make resounding changes in the way the teaching-learning process has been developing. Unesco (2020) reports that the pandemic has affected "1.6 billion students in more than 190 countries on all continents. School and other educational closures have affected 94% of students worldwide, a figure that rises to 99% in low- and lower-middle-income countries."